B-Cell Precursor–Acute Lymphoblastic Leukemia With EBF1-PDGFRB Fusion Treated With Hematopoietic Stem Cell Transplantation and Imatinib: A Case Report and Literature Review. Issue 1 (January 2021) - Sakurai, Yukari; Sarashina, Takeo; Toriumi, Naohisa; Hatakeyama, Naoki; Kanayama, Takuyo; Imamura, Toshihiko; Osumi, Tomoo; Ohki, Kentaro; Kiyokawa, Nobutaka; Azuma, Hiroshi
Abstract : A 9-year-old girl was diagnosed with B-cell precursor–acute lymphoblastic leukemia (BCP-ALL). Although she entered remission after induction therapy, she relapsed 15 months after maintenance therapy cessation. Since further investigation revealed EBF1-PDGFRB fusion, her condition was treated as BCR-ABL1 –like acute lymphoblastic leukemia. She was started on a tyrosine kinase inhibitor, imatinib, and chemotherapy and underwent umbilical cord blood transplantation following reduced intensity conditioning. She has remained in complete remission for 36 months after cord blood transplantation. This case demonstrates the successful use of a tyrosine kinase inhibitor to treat BCP-ALL with a fusion transcript and highlights the need for a standardized treatment protocol.